The Comparison of Electrodialysis and Nanofiltration in Nitrate Removal from Groundwater - J Touir; S Kitanou; M Zait; S Belhamidi; M Belfaquir; M Tahaikt; M Taky; A Elmidaoui (Indonesian Journal of Science and Technology, 2021)
Nitrate groundwater contamination is of major interest all over the world. This problem arises in agricultural regions across Morocco. An excess amount of nitrate causes a serious problem in urban water networks and human health. Because of these health risks, considerable attention has been paid to find effective treatment processes to reduce nitrate concentrations to safe levels. The World Health Organization has set an acceptable level for nitrate in drinking water at 50 mg/L. The aim of this study is to reduce the nitrate concentration from groundwater using two membrane processes: Electrodialysis (ED) and Nanofiltration (NF). Efficiencies of these two technologies are compared in respect to nitrate ions removal, cost process and final quality of water. The results of technologies show that, for electrodialysis standards level can be achieved for a demineralization rate of 15% and the physico-chemical quality of the produced water is satisfactory. For nanofiltration we obtain a nitrate removal of 90% but the produced water is very de-mineralized and must be remineralized.